NASREDDİN HOCA FIKRALARINDA İNSANI ANLAMA/MAK - Şenocak, Ebru (Tuzla Belediyesi, 2016)
Nasreddin Hoca, yalnızca Anadolu'da ve Türk dünyasında değil, bütün dünyada sevilen bir mizah/ironi ustası ve bilge kahramandır. Güldürürken düşündüren fıkralarını okuyan/dinleyen her insan kendisine dair olumlu ve yapıcı mesajlar çıkarır. Toplum yaşantısının renkli karelerini fıkralarında ele alan Nas-reddin Hoca, bir anlamda kişiye kendisini izleme fırsatı vererek, hayatını düzene koymasına yardımcı olur. Çünkü o, evrensel anlamda aklın ve gönlün orta yolunu mizahla buluşturmuş "yüce birey" dir. Toplum yaşantısındaki sağlıklı iletişim ve mutluluğun kişinin başta kendisiyle barışık olmasına bağlı olduğuna değinen Nasreddin Hoca, fıkralarında, sık sık insanı anlama sanatı ve empatinin önemi üzerinde durur. Bazen kişi ve kurumları mizah/ironi oklarına tutarak nakavt ederken, bazen de empati kurarak güçsüzü koruyup kollayarak rencide olmasını engeller. Biz bu çalışmamızda, insanı anlama sanatı ve insanı anlamamak konulu fıkralarda, Nasreddin Hoca'nın, empati kurma, iletişim becerisi ve toplumsal yaşamı kaostan kozmosa dönüştürme önerilerini değerlendireceğiz.

Nasreddin Hodja, is a master of humor/irony and a wise hero who is loved not only in Anatolia and in the Turkish world, but all over the world. Each person reading/listening his jokes, which makes someone think while entertainning, finds out positive and constructive messages about himself. De-aling with the colored patterns of social life in his jokes, Nasreddin Hodja, in a sense helps the person to tidy up his life, by finding the opportunity of monito-ring himself. Because, he is an “almighty individual” who has brough the happy medium of mind and heart together with humor in the universal sense. Nasreddin Hodja, who mentions that the healthy communication and happiness in social life in the first instance depends on person’s being at peace with himself, in his jokes, often lays emphasis on the importance of art of understanding the human and the empathy. While sometimes knocks out persons and institutions by the arrows of humor/irony, sometimes he prevents the weak from being hurt, by developing empathy and by protecting them. In our study, in the jokes themed on art of understanding people and not to understand people, we will evaluate the communication skills of Nasreddin Hodja, his ability in developing empathy and his suggestions for transforming the social life from chaos into cosmos.
NOT/UNDERSTANDING THE PEOPLE IN THE JOKES OF NASREDDIN HODJA